Bioinorganic Synthesis of Sodium Polytungstate/Polyoxometalate in Microbial Kombucha Media for Precise Detection of Doxorubicin. (8th August 2022) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Bahrani, Sonia; Sadrmousavi-Dizaj, Asma; Arjmand, Omid; Omidifar, Navid; Lai, Chin Wei; Chiang, Wei-Hung; Gholami, Ahmad
Abstract : In this study, we have developed a new platform of polyoxometalate as a biocompatible and electrosensitive polymeric biosensor for the accurate detection of doxorubicin. For this purpose, we used a green synthesis approach using tartaric acid, glutamic acid, and kombucha solvent. Thanks to its bioinorganic components, the biogenic approach can chemically modify and improve the performance of the biosensor, which was experimentally confirmed. Our results showed excellent sensitivity (175.72 μ A· μ M −1 ·cm −2 ), low detection limit (DL, 8.12 nM), and low quantification limit (QL, 0.056 μ M) when the newly developed biosensor was used. The results also show that the biosynthesized biosensor has improved performance in detecting DOX in the biological fluid with an accuracy of more than 99% depending on the components used, which underlines the high efficiency of the biosensor produced. Considering the body's physiological condition, the biosensor fabricated as a biocompatible component can show high efficiency. Therefore, its applicability for clinical use still needs to be studied in detail.